Improved Route Discovery Based on Constructing Connected Dominating Set in MANET - Zifen Yang; Deqian Fu; Lihua Han; Seong Tae Jhang (International Journal of Distributed Sensor Networks)
A mobile ad hoc network (MANET) is widely applied in various urgent scenarios, benefiting from its feature that the hosts can communicate with each other without any physical infrastructure. An efficient routing function plays a critical role in MANET, and routing based on CDS is a promising approach. In this paper, a novel approach is proposed to obtain a stable routing path and prolong lifetime of MANET, by integrating three factors such as energy, mobility, and degree for the status of node minimum connected dominating set (SoN-MCDS). Extensive simulations show that the proposed protocol is superior to other classical ones in terms of lifetime and low energy consumption.